2022
DOI: 10.1016/j.lwt.2021.112684
|View full text |Cite
|
Sign up to set email alerts
|

Identification of lactoferrin-derived peptides as potential inhibitors against the main protease of SARS-CoV-2

Abstract: COVID-19 is a global health emergency that causes serious concerns. A global effort is underway to identify drugs for the treatment of COVID-19. One possible solution to the present problem is to develop drugs that can inhibit SARS-CoV-2 main protease (M pro ), a coronavirus protein that been considered as one among many drug targets. In this work, lactoferrin from Bos taurus L. was in silico hydrolyzed. The bioactivity, water solubility, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 45 publications
0
21
0
Order By: Relevance
“… 984 Zhao et al’s docking studies identified GSRY among lactoferrin-derived peptides is potent to Mpro. 985 Behzadipour et al evaluated the SARS-CoV-2 Mpro inhibitory activity of 326 di- and tripeptides from the proteolysis of bovine milk proteins by docking. 986 Some works 974 , 987 , 988 aimed to repurpose peptides from seed proteins to targets Mpro, S protein, and PLpro.…”
Section: Methods and Approachesmentioning
confidence: 99%
“… 984 Zhao et al’s docking studies identified GSRY among lactoferrin-derived peptides is potent to Mpro. 985 Behzadipour et al evaluated the SARS-CoV-2 Mpro inhibitory activity of 326 di- and tripeptides from the proteolysis of bovine milk proteins by docking. 986 Some works 974 , 987 , 988 aimed to repurpose peptides from seed proteins to targets Mpro, S protein, and PLpro.…”
Section: Methods and Approachesmentioning
confidence: 99%
“…There are three proteins on the membrane of SARS-CoV-2, namely S protein, membrane protein (M protein), and envelope protein (E protein). After silico hydrolysis of bovine lactoferrin (bLF), bLF hydrolytic peptide GSRY with good solubility that can bind to M protein was identified by the molecular docking method ( 72 ). The molecular docking also demonstrated that LF can not only bind to CTSL and affect the virus internalization of SARS-CoV-2 ( 73 ) but also target SARS-CoV-2 S protein and block its binding to ACE2 ( 74 ).…”
Section: Sars-cov-2 Rna Positive In Breastmilk But Without Infectious...mentioning
confidence: 99%
“…In addition, the solubility results indicated that all these compounds exhibited optimal or good solubility (Tables 3, S1 and S2). Drug failure is generally caused by insufficient absorption and distribution of the drug due to low solubility [15]. Thus, marine aldehyde derivatives could be selected as new drug candidates because of their valuable absorption and solubility levels.…”
Section: Adme/tox Analysis Of the Marine Aldehyde Derivativesmentioning
confidence: 99%
“…ADME/Tox modeling can aid in the success of drugs in clinical trials [13]. In addition, molecular-docking-based virtual screening identifies compounds with the highest binding affinities and correct binding modes [7,15].…”
Section: Introductionmentioning
confidence: 99%